Does a Negative Rapid Diagnostic Test for Detection of Candida Bloodstream Infection Lead to Less Antifungal Use?. (4th October 2017) - Bhowmick, Tanaya; Sharma, Rashi; Weinstein, Melvin; Narayanan, Navaneeth; Kirn, Thomas
Abstract: Background: Candida species are the fourth leading cause of nosocomial bloodstream infections in the United States, however incidence is low and most patients who receive empiric treatment do not actually have candidemia. Unfortunately, detection, identification and susceptibility testing using standard instrumented blood culture systems and routine microbiological techniques takes 4–10 days. Astute clinicians may empirically treat patients with antifungal therapy (AFT) prior to having any results, often leading to unnecessary coverage for candida infection for up to 10 days. The T2 Candida Panel is an FDA-approved assay that rapidly detects the presence of 5 Candida species directly from whole blood in 3–5 hours. We determined whether AFT decisions were altered based on negative (neg) results of a T2 assay. Methods: We performed a retrospective chart review of the first 50 patients at our institution from March 1, 2016 to March 1, 2017 with a neg T2 Candida assay result (data collection is ongoing). If a patient had multiple valid T2 assays, only the first result was used for analysis. The patients' medical records were reviewed for use and duration of empiric AFT, results of blood cultures, treatment modification, underlying illness, risk factors for candida infection, length of stay, and 14-day mortality from the time of the T2 assay. Results: Twenty-four patients were never started on AFT. Of the 26 who received AFT, it was stopped in 15 (57%) following T2 results (median time to stop empiric AFT = 2 days (1–16)). The reasons for continuing AFT in the cases of neg T2 assays included hematologic malignancy patients who were on long-term prophylaxis with antifungals (6 patients), empiric use in a case of severe sepsis (1 patient), and positive culture results despite neg T2 assay in 4 patients: 1 patient with C. lusitaniae in blood culture, 1 patient with C. parapsilosis from positive culture of medical device, 1 patient with neg T2 but positive blood cultures from 2 days prior for C. albicans (was on antifungal therapy at time of test), 1 patient with C. guilliermondii in blood culture. Conclusion: We conclude that a neg T2 Candida assay affects empirical use of AFT in certain patient populations and may be useful in controlling the overuse of antifungal agents. Disclosures: All authors: No reported disclosures.